Seroprevalence of Hepatitis B Under Age Six - Şahin, Yasin; Aydın, Derya (Fırat University, 2005)
Objectives: In this cross-sectional study, we aimed to investigate hepatitis B seroprevalence in children, under 6 years old, referring to outpatient clinics of pediatrics. Materials and Methods: Between June 2004-March 2005, 240 patients without jaundice, under age six years, were investigated at the pediatrics department. Children were grouped according to their ages as 15 months, 2 years, 3 years, 4 years, 5 years and 6 years. After obtaining informed consent of their parents, we collected 3 cc venous blood samples and determined Hepatitis B markers (HBsAg, anti-HBs, anti-HBc, HBeAg, anti- HBe) in each sample by Enzyme-Linked Immunosorbent Assay (ELISA) method. Results: We found anti-HBs positivity in 170 children (70.8%). Ninety-three of them (54.7%) had been vaccinated against Hepatitis-B, while 77 of them (45.3%), had had hepatitis B infection previously. Only three children (1.25%) had HBsAg positivity. The rate of vaccination in all children was determined 38.75%. Conclusion: Although this study was performed on children including routine hepatitis B vaccination program of Ministry of Health Services, the rate of vaccination was determined 38.75%. Importance of educational status of parents, necessity of public education about routine hepatitis B vaccine and the need of seroprevalence studies were emphasized. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Kesitsel tipteki bu çalışmada, çocuk polikliniğine başvuran 6 yaş ve altı çocuklarda hepatit B seroprevalansını saptamak amaçlandı. Gereç ve Yöntem: Haziran 2004-Mart 2005 tarihleri arasında uygulanmış olan kesitsel tipteki bu çalışma, çocuk polikliniğine sarılık dışı nedenlerle getirilen 6 yaş altı 240 çocukta gerçekleştirildi. Çalışma kapsamındaki çocuklar yaşlarına göre; 15 ay, 2 yaş, 3 yaş, 4 yaş, 5 yaş ve 6 yaş olmak üzere gruplara ayrıldı. Araştırma kapsamına giren çocukların anne ve babalarından araştırma için izin alındıktan sonra, çocuklardan 3 cc'lik venöz kan örneği alındı ve Hepatit B virüsü (HBV)'nün serolojik belirleyicileri (HBsAg, anti-HBs, anti-HBc, HBeAg, ve anti-HBe) Enzyme-Linked Immunosorbent Assay (ELISA) yöntemiyle test edildi. Bulgular: Çalışmaya alınan çocukların 170'inde (%70.8) anti-HBs pozitifliği saptandı. Bunlardan 93'ü (%54.7) aşılı, 77'si (%45.3) ise hepatit B enfeksiyonu geçirmiş idi. Sadece üç çocukta (%1.25) HBsAg pozitifliği saptandı. Tüm çocuklarda aşılanma oranı %38.75 tespit edildi. Sonuç: Bu çalışma, Sağlık Bakanlığı'nın rutin Hepatit B aşılama programı dahilinde olan çocuklar üzerinde yapılmasına rağmen, aşılanma oranı %38.75 tespit edildi. Anne baba eğitiminin önemine, rutin hepatit B aşısı konusunda halkı bilgilendirmenin gerekliliğine, sağlıklı çocukların izlenmesinde HBV açısından yakın takibine ve daha geniş çaplı seroprevalans çalışmalarına gereksinim olduğuna dikkat çekilmiştir. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Altı Yaş ve Altı Çocuklarda Hepatit B Seroprevalansı